Drinking Water Quality at Academic Institutions of Tangail Municipality (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to explore the drinking water quality at some selected academic institutions of Tangail municipality during the period of August to September, 2012. For this, an investigation was carried out to study the standard water quality parameters such as pH, EC, TDS, Pb, As, Fe and E. coli concentration of the five academic institutions. In general, there were no major differences found in pH, EC and TDS values among the studied stations and not exceeded the recommended thresholds. In case of heavy metal content, very trace amount of Arsenic (0.0071ppm) was recorded from all selected institutions. In contrast, average lead concentration (0.307xppm) was much higher than all acceptable standard limits and most risky position was taken by station-3 (0.46ppm). Similar to Pb, average Fe concentration (0.255ppm) was five times higher than the acceptable value of EU standard but not exceeded BD standard value. All the samples were E.Coli bacteria free.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22074 J. Environ. Sci. & Natural Resources, 6(1): 247-252 2013